Does authentic leadership stimulate organizational citizenship behaviors? The importance of affective commitment as a mediator. Issue 2 (11th October 2021) - Ribeiro, Neuza; Duarte, Ana Patrícia; Filipe, Rita; David, Rajasekhar
Abstract : Purpose: This study aims to examine the impact of authentic leadership (AL) on employees' organizational citizenship behaviors (OCB) by investigating the mediating effect of affective commitment (AC). Design/methodology/approach: Data were collected on 194 leader-follower dyads in diverse organizations, using individual surveys. Followers reported their perceptions of AL and their AC, and leaders assessed each follower's level of OCB. Findings: The results support the research hypotheses proposed, confirming that employees' perceptions of AL are positively related to both their AC and OCB. Moreover, AC completely mediates the relationship between AL and OCB, indicating that authentic leaders increase employees' affective bonds to their organization, and therefore, strengthen workers' tendency to engage in OCB. Research limitations/implications: Additional studies with larger samples are needed to clarify more fully not only AL's influence on OCB but also other psychosocial variables affecting this relationship. Practical implications: The findings suggest that organizations can foster employees' AC and OCB by encouraging managers to adopt a more AL style. Authentic leaders are likely to focus on the collective as they care about their teams, the wider organization and even society's welfare and sustainability. Social implications: Growing concerns about sustainability and business ethics and the crisis of trust in organizations can be addressed through further research on positive leadership forms such as AL. This study's findings suggest that AL fosters employees' affective bond to organizations and their willingness to engage in OCB, which are two indicators related to organizational sustainability. Originality/value: This study integrated AL, AC and OCB into a single research model, thereby extending previous investigations. In addition, the data were collected from two sources (i.e. both leaders and followers in dyads) to minimize the risk of common-method variance.